The Imperative of Systems Thinking Approach in Driving Food Systems Transformation through Science and Innovation - Olanike K. Adeyemo FAS (The Proceedings of the Nigerian Academy of Science)
As the world became progressively aware that increasing production did not solve global hunger and health problems, the issue of the environmental and social costs of focusing solely on food security and nutrition came to the fore. The term ‘food systems transformation’ was introduced as a radical idea of rethinking the key outcomes of food systems. A complete rethink of the attributes of food systems, including its purpose, rules, and power structures. Food system transformation processes would ideally reshape the way a food system is organized for the desired outcomes: food security, healthy diets, economic wellbeing, social wellbeing and environmental sustainability.